Increased compulsory school leaving age affects secondary school track choice and increases dropout rates in vocational training schools - Anna Adamecz-Völgyi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2018)
This paper examines the effects of increasing the compulsory school leaving (CSL) age from 16 to 18 in Hungary using a regression discontinuity design (RDD) identification strategy. The new CSL age was introduced for those entering their first year of elementary school in 1998. Identification is based on compliance with the age of elementary school start rule. Compliance with the age rule creates a discontinuity in the probability of starting school under the higher CSL age regime around a cutoff date of birth. The treated cohort had known about the change since age 6. This fact allows for testing on how the increase affected forward-looking decision making about secondary school track choice which occurs at age 14. The legislation change resulted in an increased probability that children would choose the academic high school track instead of vocational training schools. At the same time, those choosing vocational training schools are more likely to drop out under the higher CSL age scheme. Potential explanations of increased dropout rates include a decrease in the quality of teaching in vocational training schools due to supply constraints, and a shift in student composition to include more students from lower socioeconomic backgrounds.
Keywords: J08; C21; I21; I26; 330; education; school choice; compulsory school leaving age; regression discontinuity design